Endovenous laser ablation for great saphenous varicose veins - Goda, Asser Abd El Hamid (International Surgery Journal, 2019)
Background: Endovenous laser ablation (EVLA) is one of the most accepted treatment options for great saphenous varicose veins. The aim of this study was to evaluate the efficacy and safety EVLA in a 12 months follow-up. Methods: Patients with symptomatic great saphenous veins (GSV) reflux were undergo EVLA. The outcome measures the efficacy and safety along the follow up period (12 months). The efficacy assessed by measuring the occlusion rate of the GSV by duplex and by measuring the improvement in the mean venous clinical severity score (VCSS) by clinical examination. The safety assessed by clinical examination to detect the complications. Results: The rate of complete occlusion in the main trunk of the great saphenous vein was 34/35 (97.1%) at 6 and 12 months. The mean VCSS scores improved significantly after the procedure at 6 and 12 months. Complications detected within 1st week as pigmentation in 3 patients, local hematoma in one patient, and paresthesia in one patient but all complications disappeared within 6 and 12 months. Conclusions: EVLA is an effective and safe procedure for the treatment of varicose great saphenous.